Rights and the City Problems, Progress, and Practice - Agrawal, Sandeep (University of Alberta Press, 2022)
Rights and the City takes stock of rights struggles and progress in cities by exploring the tensions that exist between different concepts of rights. Sandeep Agrawal and the volume's contributors expose the paradoxes that planners and municipal governments face when attempting not only to combat discriminatory practices, but also advance a human rights agenda. The authors examine the legal, conceptual, and philosophical aspects of rights, including its various forms-human, Indigenous, housing, property rights, and various other forms of rights. Using empirical evidence and examples, they translate the philosophical and legal aspects of rights into more practical terms and applications. Regionally, the book draws on municipalities from across Canada while also making broad international comparisons. Scholars, policy makers, and activists with an interest in urban studies, planning, and law will find much of value throughout this volume. Contributors: Sandeep Agrawal, Rachelle Alterman, Sasha Best, Alexandra Flynn, Eran S. Kaplinsky, Ola P. Malik, Jennifer A. Orange, Michelle L. Oren, Renée Vaugeois. Afterword by Benjamin Davy